(untitled) (Ocean and Coastal Research, 2024)
Plastic bags, bottles, packing tapes, and fishing lines are at the forefront of the discussion on plastic pollution inthe oceans. However, scientific interest on the role of cotton buds in such context is rapidly increasing, as theseobjects continue to be widely used and discarded improperly. Therefore, this study aimed to determine theabundance and fate of cotton buds as a case study in the Küçükçekmece Lagoon. At two sampling stations,the pebbly beach and the rocky beach, a total of 854 cotton buds were found over the course of six months withan average value of 71.16 litters m-2 per month. The similarity of months of occurrence in summer and autumnwas statistically significant. However, in November and December, when meteorological conditions were moresevere, significant similarity was observed. Furthermore, the results of the potential environmental hazard, riskassessment, and carbonyl index were used to provide answers to the main problems of cotton bud pollution.Consequently, the hazard level was classified as either III or IV and the risk level was determined unfriendly.In total, 44.5% of the samples had a high level of oxidation. EDX analysis also confirmed that the biofilminfluenced the accumulation of metals on the plastic surface. Overall, the results have addressed the issues thatshould be considered in improving the management strategies for plastics, which can be implemented to reducethe environmental impact of plastics and achieved the main objective of raising awareness on the accumulationof plastic waste generated by anthropogenic activities in coastal areas.